Revisiting the Weberian conceptual framework and its relevance for analysing ethnic and racial relations in contemporary times - Mendes, M. M. (Intersections. East European Journal of Society and Politics, 2024)
Max Weber was a forerunner and one of the most innovative sociologists of his time. Among the many and diverse contributions to his extensive work, this article aims to highlight his importance and pioneering spirit in the analysis of ethnic and racial relations. Based on the fact that Romani people (known as Ciganos in Portugal) comprise the most numerous minority in Europe (10–12 million), we aim to discuss the relevance and limits of certain conceptual tools and forms of (self) categorization of Ciganos/Roma, namely those based on racial and ethnic phenomena, revisiting Max Weber’s writings. Based on a qualitative study carried out on Portuguese Ciganos/Roma, using in-depth interviews of women and men resident in the Lisbon Metropolitan Area, we seek to question the pertinence of these forms of categorization when applied in operative and empirical ways to Ciganos/Roma persons in contemporaneity.